Peran Dakwah Kelas a Letter to Allah (ALETTA) dalam Pengamalan Agama Melalui Doa - Mulki B. Azkiani; Asep Ahmad Siddiq (Jurnal Riset Komunikasi Penyiaran Islam, 2022)
Abstract. a Letter to Allah (ALETTA) is an online class that explores the meaning of the 40 dua of Robbana in the Qur'an. Presented online through the website as well as Mosfeed which is equipped with a video storage feature so that users can replay ALETTA classes anywhere as long as they are connected to the internet network. This class is made by data and research so that the presentation can achieve the expected goals. Being able to present a class that is comfortable for the eyes and ears without violating sharia is a principle for the ALETTA’s class maker, namely Syameela. Based on this phenomenon, this research is limited by the following problem formulations: (1) How is the process of proselytizing the ALETTA class to the participants? (2) How do participants understand dua after attending the ALETTA class? (3) What is the impact on participants in practicing religion through dua after attending the ALETTA class? The researcher uses a qualitative method with a case study approach to examine the object of research in depth. The informants selected in this study were the director of the ALETTA class and two active participants in the class ALETTA. Data collection techniques were used in this study through observation and interviews. The data analysis technique used in this research is the inductive and descriptive analysis technique. The results of this study are: The role of ALETTA class da'wah in practicing religion through dua to participants is observed from (1) the da'wah process carried out by Syameela based on research-innovation consisting of pre-production, production, and post-production stages; (2) participants' understanding dua of Robbana and various important factors related to dua; (3) the impact of ALETTA on participants changing the meaning, experience, and practice in dua Abstrak. a Letter to Allah (ALETTA) merupakan kelas daring yang menyelami makna 40 doa Robbana di dalam Al-Qur’an. Disajikan secara daring melalui laman sekaligus aplikasi Mosfeed versi premium yang dilengkapi fitur penyimpanan video sehingga pengguna dapat memutar ulang kelas ALETTA di manapun selama terkoneksi dengan jaringan internet. Kelas ini dibuat by data and research agar penyajiannya dapat mencapai tujuan yang diharapkan. Mampu menghadirkan kelas yang nyaman bagi mata dan telinga tanpa melanggar syariat Islam adalah prinsip bagi tim pembuat kelas ALETTA yakni Syameela. Berdasarkan fenomena tersebut, maka penelitian ini dibatasi oleh rumusan permasalahan berikut: (1) Bagaimana proses dakwah kelas ALETTA kepada peserta? (2) Bagaimana pemahaman peserta mengenai doa setelah mengikuti kelas ALETTA? (3) Bagaimana dampak terhadap peserta dalam pengamalan agama melalui doa setelah mengikuti kelas ALETTA? Peneliti menggunakan metode kualitatif dengan pendekatan studi kasus guna mencermati objek penelitian secara mendalam. Informan yang dipilih dalam penelitian ini adalah director kelas ALETTA dan dua orang peserta aktif kelas ALETTA. Teknik pengumpulan data yang digunakan dalam penelitian ini melalui observasi dan wawancara. Adapun teknik analisis data yang digunakan dalam penelitian ini adalah teknis analisis induktif dan teknik analisis deskriptif. Hasil dari penelitian ini adalah: Peran dakwah kelas ALETTA dalam pengamalan agama melalui doa terhadap peserta dicermati dari (1) proses dakwah yang dilakukan Syameela berbasis riset-inovasi terdiri dari tahap pra produksi, produksi, dan pasca produksi; (2) pemahaman peserta atas doa Robbana serta berbagai faktor penting terkait doa; (3) dampak ALETTA bagi peserta mengubah pemaknaan, pengalaman, dan pengamalan dalam berdoa.